Anorectal Malformation: State of the Art in Translating Experimental Research to the Bedside - Martins, José Luiz; Macedo, Maurício; Montero, Edna Frasson de Souza (European Journal of Pediatric Surgery, 2019)
The embryology of anorectal malformation (ARM) is a controversial issue. The study in humans is difficult due to the scarcity of fetuses with this anomaly. Therefore, ARM animal models, naturally obtained or induced by drugs, have been employed to understand physiopathology and possible treatments. Pigs, rabbits, rats, and mice have been employed as animal models. Additionally, many drugs have been used with this purpose: Etretinate, Ethylenethiourea, and Adriamycin. The animal more frequently used is the rat because of good reproducibility, low cost, and easy handling. Pig is a good model, but it is expensive, and difficult to handling and lodging. Concerning the drugs, Adriamycin promotes a more severe ARM compared with Ethylenethiourea. The models of ARM are of value in the understanding of the embryologic development. Nowadays, researches are aimed at identifying the molecular mechanism of this process, providing the basis for the application of tissue engineering in future experiments with ARM.
Keywords: anorectal malformations; experimental models; ethylenethiourea; adriamycin